Isolation and in vitro characterization of murine young-adult long bone skeletal progenitors - Loopmans, Shauni; Stockmans, Ingrid; Carmeliet, Geert; Stegen, Steve (Frontiers in Endocrinology, 2022)
Skeletal stem and progenitor cells (SSPCs) constitute a reservoir of bone-forming cells necessary for bone development, modeling and remodeling, as well as for fracture healing. Recent advances in tools to identify and isolate SSPCs have revealed that cells with multipotent properties are present not only in neonatal bone, but also in adult bone marrow and periosteum. The long bone metaphysis and endosteum have been proposed as an additional SSPC niche, although in vitro approaches to study their cellular and molecular characteristics are still limited. Here, we describe a comprehensive procedure to isolate and culture SSPCs derived from the metaphysis and endosteum of young-adult mice. Based on flow cytometry analysis of known SSPC markers, we found the presence of putative multipotent SSPCs, similar to neonatal bone tissue. In vitro, metaphyseal/endosteal SSPCs possess self-renewing capacity, and their multipotency is underscored by the ability to differentiate into the osteogenic and adipogenic lineage, while chondrogenic potential is limited. Expansion of metaphyseal/endosteal SSPCs under low oxygen conditions increases their proliferation capacity, while progenitor properties are maintained, likely reflecting their hypoxic niche in vivo. Collectively, we propose a validated isolation and culture protocol to study metaphyseal/endosteal SSPC biology in vitro.